Avifaunal diversity and bird community responses to man-made habitats in St. Coombs Tea Estate, Sri Lanka - J. Dananjaya Kottawa-Arachchi; Rajika N. Gamage (Journal of Threatened Taxa, 2015)
A survey on birds was conducted at St. Coombs Tea Estate, Talawakelle, Sri Lanka with the objective of assessing the avifaunal diversity of a given tea plantation ecosystem. Bird populations were sampled in man-made habitats such as home garden, wetland, tea plantation, Eucalyptus plantation and small scale reservoir. Hundred-and-twenty counts were made for each habitat and in addition, activities of birds, feeding habits and food recourses were also observed. A total of 87 species, including 11 endemic and 11 migrant species of birds, was recorded, which included one globally threatened species, Kashmir Flycatcher Ficedula subrubra and 16 nationally threatened species. A majority of the bird species were observed in home gardens (75%), followed by reservoirs (57%), wetlands (48%), tea plantations (43%) and in Eucalyptus plantations (23%). Home gardens support bird diversity while the species richness of endemic bird species increases thereby enabling these findings to be used as guidelines in long term conservational practices. Several conservation measures such as increasing plant diversity, introduction of shade trees and prevention of fire are recommended to conserve and enhance avifaunal diversity in tea plantations.